Neglected Trans-Scaphoid Volar Perilunate Dislocation with Post-Operative Complex Regional Pain Syndrome: A Case Report (Global Journal of Medical Research, 2020)
We present the case report of a 30-year-old male who fell from a height of 15 feet on his palmar-flexed right wrist and came to us 1 month after the injury. He had a swollen, stiff wrist with painful movements and no neurovascular deficit. X-rays showed a trans-scaphoid volar perilunate dislocation. We used the volar approach for open reduction and internal fixation with a headless screw for scaphoid fracture and scapho-lunate and capito-lunate K-wires for intercarpal instability. The wrist was immobilised in a below-elbow POP slab for 6 weeks after which the Kwires were removed. The patient unfortunately developed complex regional pain syndrome (CRPS), which can be attributed to his late presentation after the injury. Active and passive range of motion exercises and contrast bath were initiated and he was kept on low dose amitriptyline. Gradually CRPS resolved and at 6-month follow-up, the patient had a wrist dorsiflexion of 30° and palmar-flexion of 45°.